MXene / ferric oxalate composite material and preparation method thereof

Through the hydrothermal composite of MXene and iron oxalate, an interwoven three-dimensional conductive network is formed, which solves the problem of interlayer stacking and insufficient conductivity of iron oxalate in MXene material, and significantly improves the conductivity and electrochemical properties of the material.

CN119742184AActive Publication Date: 2025-04-01CHANGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411938955.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

During use, MXene materials are prone to stacking between sheets, resulting in a decrease in active surface area and hindered ion transport, affecting its electrochemical performance. In addition, the conductivity of iron oxalate is poor. When used as an electrode material alone, its rate performance and charge and discharge speed are limited.

Method used

MXene and iron oxalate were combined by hydrothermal method, and iron oxalate was loaded on the surface and layer of MXene under high temperature and high pressure, so that MXene and iron oxalate were cross-combined to form an interwoven three-dimensional conductive network.

Benefits of technology

It improves the conductivity of the material, improves the ion transfer rate, improves the electrochemical performance of the material, reduces the stacking effect between MXene, and enhances the structural stability of the composite material during the charge and discharge cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742184A_ABST
    Figure CN119742184A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of supercapacitor electrode materials, in particular to an MXene / ferric oxalate composite material and a preparation method thereof. The preparation method comprises the following steps: preparing an MXene nanosheet; and mixing and stirring the MXene suspension with FeSO4. 7H2O, ascorbic acid and H2C2O4. 2H2O, and then putting the mixture into a muffle furnace for hydrothermal reaction to obtain the MXene / ferric oxalate composite material. MXene and ferric oxalate are compounded through a hydrothermal method, the conductivity of MXene is improved, a three-dimensional conductive network is generated after in-situ compounding of MXene and ferric oxalate, and the conductivity of the composite material is further improved; under the hydrothermal condition, the crystallinity is increased along with temperature rise, and after the ferric oxalate and MXene are compounded in a crossed mode, the ion transmission rate is increased, and the performance of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to a MXene / ferric oxalate composite material and a preparation method thereof. Background Art

[0002] Supercapacitors have advantages such as high output power, fast charge and discharge capability, wide operating temperature range and ultra-long cycle, but their application is limited by low energy density. Electrode materials are components of supercapacitors, and their selection and optimization are crucial to improving the performance of supercapacitors.

[0003] In recent years, MXene materials have become a hot topic in the research of supercapacitor electrode materials due to their excellent electrochemical properties. MXene is a type of two-dimensional material composed of transition metal carbides, nitrides or carbonitrides. MXene has metal-like conductivity, which can significantly improve the rate performance of supercapacitors. In addition, its two-dimensional sheet structure provides abundant active sites, which is conducive to ion adsorption and storage. MXene surfaces often carry active groups such as -OH, -F, and -O. These groups can store more charge in pseudocapacitive reactions, further improving the specific capacity.

[0004] However, in practical applications, due to the two-dimensional sheet structure of MXene, the stacking phenomenon between sheets is easy to occur during use, resulting in a reduction in active surface area and obstruction of ion transmission, thus affecting its electrochemical performance. The stacking between sheets may also cause mechanical structural instability and reduce the cycle life of supercapacitors. Ferric oxalate has gradually become a highly regarded capacitor material due to its low cost, porous structure and high specific capacity, but ferric oxalate also has the problem of poor conductivity. When used alone as an electrode material, its rate performance and charge and discharge speed are limited.

[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0006] The technical problem to be solved by the present invention is: to provide a MXene / ferric oxalate composite material and a preparation method thereof, to compound MXene and ferric oxalate by a hydrothermal method, to load the ferric oxalate on the surface and interlayer of MXene under high temperature and high pressure, so that MXene and ferric oxalate are cross-compounded to form an interwoven three-dimensional conductive network, thereby further improving the conductivity of the material, improving the ion transmission rate, and achieving the improvement of the electrochemical performance of the material.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing a MXene / ferric oxalate composite material comprises the following steps: S01: Preparation of MXene nanosheets: LiF and Ti3AlC2 are slowly added to the HCl solution in sequence and stirred evenly, and then transferred to an oil bath for heating and stirring etching; the solution obtained after etching is washed by centrifugation with HCl and deionized water respectively, and then placed in an ultrasonic crusher with protective gas and ice bath ultrasonication, and then placed in a centrifuge for centrifugation to obtain the upper suspension; Among them, by etching Ti3AlC2 (MAX phase) with HCl solution and LiF, aluminum elements were removed from Ti3AlC2 to generate layered MXene nanosheets (Ti3C2Tx, Tx represents surface groups such as -OH, -F, etc.). The MXene layer was then further peeled off by ultrasonic crushing to obtain MXene nanosheets with high specific surface area and abundant active surface sites. These sites provide more reactive areas for subsequent iron oxalate composites.

[0008] Preferably, in step S01, the mass ratio of LiF to Ti3AlC2 is 1:1-1.2. LiF releases F in HCl solution. - , these F - With H + The synergistic effect can selectively etch the Al layer in Ti3AlC2 to generate MXene nanosheets. - Insufficient LiF will result in incomplete etching of the Al layer, affecting the yield and quality of MXene. By setting the mass ratio of LiF to Ti3AlC2 between 1:1 and 1.2, it can ensure that there is enough F in the reaction. - Participate in etching while avoiding wasting too much LiF.

[0009] Preferably, in step S01, the heating time of the oil bath is 48-52 hours, and the heating temperature of the oil bath is 38-42°C. The etching reaction of Ti3AlC2 is a relatively slow process, and it takes time for F - With H + The ions diffuse fully and react chemically with the Al layer in Ti3AlC2. Under moderate temperature and time conditions, the etching reaction can proceed more smoothly, reducing excessive damage to the MXene layered structure. If the temperature is too high or the time is too long, F - This may cause further etching of the Ti3C2 matrix, resulting in interlayer stacking and a reduction in active sites. By optimizing this interval, the layered characteristics and high specific surface area of ​​MXene can be retained.

[0010] Preferably, in step S01, when HCl is used for centrifugal washing, the centrifugal speed of HCl is 3000-4000 rpm, and the centrifugal time is 3-5 min. The main purpose of HCl centrifugal washing is to remove byproducts produced during the etching reaction. If the centrifugal speed is too low, impurities may not be effectively separated, resulting in an increase in the number of subsequent washings and a waste of resources; if the centrifugal speed is too high or the time is too long, a large shear force may be generated on the sheet, resulting in damage or stacking of the sheet, affecting the specific surface area and active sites of the material.

[0011] Preferably, in step S01, when the deionized water is centrifuged for washing, the centrifugal speed of the deionized water is 3500-6000 rpm; the centrifugal time is 4-6 min. After the HCl washing is completed, some acidic impurities and incompletely separated Al may still remain in the solution. 3+ Ions, salt byproducts, and a small amount of residual HCl. Washing with deionized water can neutralize and completely remove these impurities and improve the purity of the MXene suspension.

[0012] Preferably, in step S01, the ice bath ultrasound time is 2 to 2.5 hours; when the upper suspension is centrifuged, the centrifugal speed of the centrifuge is 3500 to 4000 rpm; and the centrifugal time is 40 to 50 minutes. Ultrasonic waves can produce high-intensity vibration and cavitation effects, which significantly weaken the interlayer bonding force of MXene, thereby achieving full exfoliation of MXene sheets. The effect of low temperature in an ice bath environment can reduce the detachment of surface groups (such as -OH, -F, etc.) caused by temperature increase, thereby maintaining the chemical activity of MXene. Through ultrasonic crushing and ice bath protection, the exfoliated MXene nanosheets have a high specific surface area and abundant active surface sites, providing an ideal basis for subsequent composite reactions.

[0013] S02: The MXene suspension was mixed with FeSO4·7H2O, ascorbic acid and H2C2O4·2H2O and stirred, and then placed in a muffle furnace for hydrothermal reaction; after centrifugal washing, the mixture was placed in a vacuum drying oven for drying, and finally a MXene / ferric oxalate composite material was obtained.

[0014] In this step, the MXene suspension is mixed with FeSO4·7H2O, H2C2O4·2H2O (oxalic acid) and ascorbic acid to generate iron oxalate (FeC2O4·2H2O) particles under hydrothermal reaction conditions. The iron oxalate particles gradually crystallize during the reaction and combine with the active surface sites of MXene to form a cross-linked three-dimensional network structure. Ascorbic acid, as a reducing agent, can effectively inhibit the Fe 2+ Oxidized to Fe 3+ , thus ensuring the stable and pure formation of ferric oxalate.

[0015] Preferably, in step S02, the molar ratio of FeSO4·7H2O, H2C2O4·2H2O and ascorbic acid is 50:25:1, and the ratio of FeSO4·7H2O to H2C2O4·2H2O is 2:1, ensuring that Fe 2+ and oxalate ions (C2O4 2- ) reacts completely to form ferric oxalate, which not only avoids the formation of by-products caused by excessive oxalate ions, but also ensures that the reactants are efficiently utilized. The molar ratio of ascorbic acid is set to 1, which acts as a reducing agent, thereby improving the purity and quality of ferric oxalate and avoiding the formation of mixtures or impurities.

[0016] Preferably, the mass ratio of FeSO4·7H2O to MXene is 1:1 to 6. When the mass ratio is 1:1, the iron oxalate content is low, and the conductive properties of MXene are more retained, which is suitable for application scenarios with high conductivity as the main feature. When the mass ratio is 1:6, the iron oxalate content is high, which enhances the structural stability and ion transmission capacity of the composite material, and is suitable for scenarios requiring higher ion storage performance.

[0017] Preferably, in step S02, during the hydrothermal reaction, the temperature of the muffle furnace is 60-100°C and the holding time is 10-12 hours. The hydrothermal reaction is a time-dependent process. The 10-12 hours of holding time can provide sufficient growth time for the iron oxalate crystals to form uniform and well-distributed particles. The mild hydrothermal conditions of 60-100°C allow the iron oxalate particles to be evenly combined with the surface and interlayer of the MXene during the generation process, avoiding particle shedding or crystallization out of control caused by high temperature. In this way, a more stable three-dimensional conductive network can be constructed, improving the uniformity and stability of the composite material.

[0018] Preferably, in step S02, during centrifugal washing, the centrifugal speed is 6000-7000 rpm, the centrifugal time is 3-5 min, and then placed in a vacuum drying oven at 40-60 ° C for 10-12 h. Through appropriate centrifugal speed and time, the MXene / ferrous oxalate composite material can settle quickly without causing the loss of fine particles due to excessive centrifugal force or too long time, thereby improving the recovery rate and yield of the material. After removing impurities and residual moisture, the chemical properties of the composite material are more stable. During long-term use, the composite material can better resist capacity decay and structural collapse, and exhibits better cycle stability.

[0019] The present invention improves the conductivity of MXene, generates a three-dimensional conductive network after in-situ compounding with ferric oxalate, further improves the conductivity of the composite material, reduces the interlayer stacking effect of MXene, and enhances the structural stability of the composite material in the charge and discharge cycle; under hydrothermal conditions, the crystallinity of ferric oxalate increases with increasing temperature, and after cross-compounding with MXene, the ion transmission rate is improved, thereby improving the performance of the composite material.

[0020] The second object of the present invention is to provide a MXene / ferric oxalate composite material prepared according to the above preparation method. The two-dimensional sheets of MXene are cross-distributed with the ferric oxalate particles to form a three-dimensional conductive network structure. The ferric oxalate particles act as a proppant to reduce the interlayer stacking effect of MXene, thereby improving the ion transfer rate and the electrochemical performance of the composite material.

[0021] The beneficial effects of the present invention are: The present invention increases the O functional groups on the surface of MXene and reduces the OH functional groups under hydrothermal conditions by compounding MXene and ferric oxalate, thereby increasing the conductivity of MXene. After compounding with ferric oxalate, the ferric oxalate first forms a nanosheet structure at low temperature, and as the temperature rises, the ferric oxalate evolves into an adhesion structure and a microrod structure, and adheres to the interlayer and surface of MXene. MXene and ferric oxalate cross-compound to form an interwoven three-dimensional conductive network, which further improves the conductivity of the material, improves the ion transmission rate, and achieves the improvement of the electrochemical performance of the material.

[0022] Due to the characteristics of MXene layered structure, it is easy to lose some active surface sites when stacked. After compounding with iron oxalate, the iron oxalate particles act as "space support", effectively reducing the interlayer stacking effect, thereby increasing the specific surface area and the number of active sites of the material. The iron oxalate particles are embedded in the interlayer and surface through in-situ compounding with MXene to form ion transmission channels, further optimizing the overall electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is the XRD pattern of the MXene / ferric oxalate composite material synthesized in Example 1.

[0025] Figure 2 This is the SEM image of the iron oxalate synthesized in Comparative Example 1.

[0026] Figure 3 This is the SEM image of the MXene synthesized in Comparative Example 2.

[0027] Figure 4 This is the SEM image of the MXene / ferric oxalate composite material synthesized in Example 2.

[0028] Figure 5 The figure is a comparison of the rate performance of Example 2 and Comparative Examples 1 and 2 obtained according to the CV curves. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0031] Example 1 A MXene / ferric oxalate composite material and a preparation method thereof are as follows: S01: First, slowly add 1g LiF into 20ml HCl (9M) solution, then slowly add 1g Ti3AlC2, and react for 48h at 290rpm and 40℃ oil bath conditions. The product after the reaction was first centrifuged at 3500rpm for 5min with 8ml 12.1M HCl. After two centrifugations, it was centrifuged from 3500rpm to 6000rpm with deionized water, increasing by 500rpm each time, and centrifuged for 5min each time. Centrifuge until the pH of the upper clear liquid is neutral, place the solution in an ice bath under N2 atmosphere, stir and ultrasonicate for 2h, then centrifuge at 3500rpm for 40min, collect the upper suspension, and obtain lamellar MXene nanosheets.

[0032] S02: Dissolve 0.193g FeSO4·7H2O and 0.0024g ascorbic acid in 15ml deionized water, recorded as solution A, dissolve 0.0876g H2C2O4·2H2O in 5ml anhydrous ethanol, drop H2C2O4·2H2O into solution A, drop 0.1g MXene into the mixed solution, mix and stir for 1h, heat in a muffle furnace at 100℃ for 12h, centrifuge and wash at 6000rpm, then put into a vacuum drying oven at 60℃ for 12h.

[0033] Example 2 A MXene / ferric oxalate composite material and a preparation method thereof are as follows: S01: First, slowly add 1g LiF into 20ml HCl (9M) solution, then slowly add 1g Ti3AlC2, and react for 48h at 290rpm and 40℃ oil bath conditions. The product after the reaction was first centrifuged at 3500rpm for 5min with 8ml 12.1M HCl. After two centrifugations, it was centrifuged from 3500rpm to 6000rpm with deionized water, increasing by 500rpm each time, and centrifuged for 5min each time. Centrifuge until the pH of the upper clear liquid is neutral, place the solution in an ice bath under N2 atmosphere, stir and ultrasonicate for 2h, then centrifuge at 3500rpm for 40min, collect the upper suspension, and obtain lamellar MXene nanosheets.

[0034] S02: Dissolve 0.386g FeSO4·7H2O and 0.0049g ascorbic acid in 15ml deionized water, recorded as solution A, dissolve 0.174g H2C2O4·2H2O in 5ml anhydrous ethanol, drop the H2C2O4·2H2O solution into solution A, drop 0.1g MXene into the mixed solution, mix and stir for 1h, heat in a muffle furnace at 100℃ for 12h, centrifuge and wash at 6000rpm, then put into a vacuum drying oven at 60℃ for 12h.

[0035] Comparative Example 1 The preparation method of ferric oxalate is as follows: S01: Dissolve 10mmol FeSO4·7H2O and 0.2mmol ascorbic acid in 45ml deionized water, recorded as solution A; dissolve 5mmol H2C2O4·2H2O in 15ml anhydrous ethanol, drop the H2C2O4·2H2O solution into solution A, mix and stir for 30min, heat in a muffle furnace at 100℃ for 12h, centrifuge and wash at 6000rpm, then dry in a vacuum drying oven at 60℃ for 12h.

[0036] Comparative Example 2 The MXene preparation method is as follows: S01: First, slowly add 1g LiF into 20ml HCl (9M) solution, then slowly add 1g Ti3AlC2, and react for 48h at 290rpm and 40℃ oil bath conditions. The product after the reaction was first centrifuged at 3500rpm for 5min with 8ml 12.1M HCl. After two centrifugations, it was centrifuged from 3500rpm to 6000rpm with deionized water, increasing by 500rpm each time, and centrifuged for 5min each time. Centrifuge until the pH of the upper clear liquid is neutral, place the solution in an ice bath under N2 atmosphere, stir and ultrasonicate for 2h, then centrifuge at 3500rpm for 40min, collect the upper suspension, and obtain lamellar MXene nanosheets.

[0037] Test Data Using Examples 1-2 and Comparative Examples 1-2 as working electrodes, activated carbon as counter electrode, Ag / AgCl as reference electrode, and 40% H2SO4 as electrolyte, three electrodes were assembled. CV was tested using an electrochemical workstation (Shanghai CHI660E).

[0038] from Figure 1 It can be seen that MXene and iron oxalate are successfully composited.

[0039] from Figure 2 It can be seen that iron oxalate presents a multi-layer rod-like structure.

[0040] from Figure 3 It can be seen that MXene has a layered structure.

[0041] from Figure 4 It can be seen that MXene and iron oxalate are cross-compounded successfully.

[0042] from Figure 5 It can be seen that the specific capacity of Example 2 at 1 mV / s is 387 F / g, while the specific capacity of Comparative Example 1 at 1 mV / s is 67 F / g, and the specific capacity of Comparative Example 2 at 1 mV / s is 317 F / g. Figure 4 It can be seen that the MXene / ferric oxalate composite material prepared by the present invention can obtain a higher specific capacitance, and the electrode material used for supercapacitors can improve its performance.

[0043] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a MXene / ferric oxalate composite material, characterized in that: The following steps are involved: S01: Preparation of MXene nanosheets: LiF and Ti3AlC2 are slowly added to the HCl solution in sequence and stirred evenly, and then transferred to an oil bath for heating and stirring etching; the solution obtained after etching is washed by centrifugation with HCl and deionized water respectively, and then placed in an ultrasonic crusher with protective gas and ice bath ultrasonication, and then placed in a centrifuge for centrifugation to obtain the upper suspension; S02: The suspension is mixed with FeSO4·7H2O, ascorbic acid and H2C2O4·2H2O, and then placed in a muffle furnace for hydrothermal reaction; after centrifugal washing, the mixture is placed in a vacuum drying oven for drying to obtain a MXene / ferrous oxalate composite material.

2. The method for preparing a MXene / ferric oxalate composite material according to claim 1, characterized in that: In step S01, the mass ratio of LiF to Ti3AlC2 is 1:1-1.

2.

3. The method for preparing a MXene / ferric oxalate composite material according to claim 1, characterized in that: In step S01, the heating time of the oil bath is 48-52 hours, and the heating temperature of the oil bath is 38-42°C.

4. The method for preparing a MXene / ferric oxalate composite material according to claim 1, characterized in that: In step S01, when HCl is used for centrifugal washing, the centrifugal speed of HCl is 3000-4000 rpm; and the centrifugal time is 3-5 min.

5. The method for preparing a MXene / ferric oxalate composite material according to claim 1, characterized in that: In step S01, when the deionized water is used for centrifugal washing, the centrifugal speed of the deionized water is 3500-6000 rpm; and the centrifugal time is 4-6 min.

6. The method for preparing a MXene / ferric oxalate composite material according to claim 1, characterized in that: In step S01, the ice bath ultrasound time is 2-2.5 hours; when the upper suspension is centrifuged, the centrifugal speed of the centrifuge is 3500-4000 rpm; and the centrifugal time is 40-50 minutes.

7. The method for preparing a MXene / ferric oxalate composite material according to claim 1, characterized in that: In step S02, the molar ratio of the FeSO4·7H2O, the H2C2O4·2H2O and the ascorbic acid is 50:25:1, and the mass ratio of the FeSO4·7H2O and the MXene is 1:1-6.

8. The method for preparing a MXene / ferric oxalate composite material according to claim 1, characterized in that: In step S02, during the hydrothermal reaction, the temperature of the muffle furnace is 60-100° C., and the insulation time is 10-12 hours.

9. The method for preparing a MXene / ferric oxalate composite material according to claim 1, characterized in that: In step S02, during centrifugal washing, the centrifugal speed is 6000-7000 rpm, the centrifugal time is 3-5 min, and then placed in a vacuum drying oven at a temperature of 40-60° C. for a drying time of 10-12 h.

10. A MXene / ferric oxalate composite material prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Hydrothermal carbon-loaded oxalyte synthesized by one-step method and preparation method thereof

    CN113600238A